تقويم مكامن التوضعات الحطامية اللازمة لإنشاء سد باشكات الركامي في منطقة الحفة باستخدام الطرائق الجيوكهربائية (Latakia University Journal -Basic Sciences Series, 2018)
يعرض هذا البحث  إمكانية استخدام الطرائق الجيوكهربائية في تحديد مكامن  التوضعات الحطامية ضمن الظروف الجيولوجية السائدة في منطقة الحفة, كمادة لإنشاء النواة الغضارية الرملية لسد باشكات الركامي, ويهدف البحث إلى: 1- تحديد التتابع الليثولوجي في مكمن التوضعات الحطامية. 2- تتبع تغير سماكات التغيرات الليثولوجية أفقيا وشاقوليا. 3 - تحديد المقاومية الكهربائية النوعية للتوضعات الليثولوجية المختلفة في المقطع المدروس وتغيراتها أفقيا وشاقوليا. 4 – تقديرالاحتياطي الاستثماري لمكمن التوضعات الحطامية. استخدمت لحل المسائل المذكورة أعلاه طريقة المقاومية باستخدام السبر الكهربائي الشاقولي, و بنتيجة تفسير القياسات الجيوكهربائية الحقلية، وضعت أربعة مقاطع جيوكهربائية لمكمن التوضعات الغضارية اللازمة لإنشاء سد باشكات الركامي. This research demonstrates the possibility  of using geoelectrical methods to locate fragments of soil deposits under the prevailing geological circumstances in Al-Haffeh region as a material to construct the mud core of the dam, moreover this geoelectrical study aims to : 1-Determine succession lithological at fragment deposits. 2- Follow the thickness change of the lithological  change vertical and horizontal. 3- Determine the specific electrical resistivity of the different lithological deposits in area section and its changes vertical and horizontal. 4-Estimate the reserve of the fragment deposits layers . Resertivity method was used to solve the above  mentioned cases using vertical electrical sounding. As a result of interpretation of the geoelectrical measurement field, four geoelectrical sections put where clay deposits lay in order to construct Bashkat accumulative dam.